EZmito: a simple and fast tool for multiple mitogenome analyses. Issue 3 (4th March 2021) - Cucini, Claudio; Leo, Chiara; Iannotti, Nicola; Boschi, Sara; Brunetti, Claudia; Pons, Joan; Fanciulli, Pietro Paolo; Frati, Francesco; Carapelli, Antonio; Nardi, Francesco
Abstract: Complete mitochondrial genome data are frequently applied to address phylogenetic/phylogeographic issues at different taxonomic levels in ecology and evolution. While sample preparation/sequencing is becoming more and more straightforward thanks to dropping costs for next-generation sequencing (NGS), data preparation and visualization remains a manually intensive step that may lead to errors if improperly conducted. We have elaborated, and here introduce, EZmito, a simple and intuitive, freely accessible Web Server aimed at automating some of these tasks. EZmito is divided into three main tools: EZpipe that assembles DNA matrices for phylo-mitogenomic analyses; EZskew that calculates genome, strand, and codon nucleotide compositional skews and EZcodon which computes Relative Synonymous Codon Usage statistics as well as amino acid usage frequency over multiple mitogenomes. Output is produced in tabular format as well as publication-quality graphics.